Description of four new species of Anelaphus Linsley (Coleoptera, Cerambycidae, Cerambycinae, Elaphidiini), correction of the spelling of species-group names, and description of the female of Anelaphus pilosus Chemsak and Noguera - Santos-Silva , Antonio (Zootaxa, 2021)
Eight species-group names of longhorned woodboring beetles in the genus Anelaphus are corrected. Four new species of Anelaphus Linsley, 1936 are described: A. steveni Santos-Silva, sp. nov., from Mexico (Chiapas); A. erici Santos-Silva, sp. nov., from Nicaragua (Granada); A. izabalensis Santos-Silva, sp. nov., from Guatemala (Izabal); and A. zacapensis Santos-Silva, sp. nov., from Guatemala (Zacapa). New Mexican state records for Anelaphus undulatus (Bates, 1880) are provided. The female of Anelaphus pilosus Chemsak and Noguera, 2003 is described for the first time, and the species is newly recorded from Guatemala. The inclusion of Anelaphus nitidipennis Chemsak and Linsley, 1968 in this genus is questioned.